My secret duke - Bennett, Sara, 1957- (Bennett, Sara, 1957. Romancing the Dukes., 2025)
"Most ladies would be thrilled to receive a proposal from a handsome duke only weeks into their first season, but Olivia is not most ladies, and the circumstances are less than ideal. After a family scandal left their coffers empty and their reputation on the rocks, Olivia must marry someone rich with an impeccable pedigree. A man with shaky finances and a taste for risky adventures is exactly wrong for her, no matter how charming his smile. Ivo Fitzsimmons, Duke of Northam, did not expect to find a wife. He planned to spend the season shoring up his smuggling enterprise and looking for new ways to keep his estate afloat. If meeting a lady like Olivia surprised him, that was nothing compared to refusing his proposal. She has feelings for him, he's sure of it. Now he'll spend the season proving he's the only man for her--if only he doesn't get arrested first."--